Chapter О роли приставок и суффиксов на ранних и поздних этапах истории славянского вида - Wiemer, Björn (Biblioteca di Studi Slavistici, 2017)
In the stem-derivational perfective-imperfective opposition of Slavic the role of prefixes and suffixes has to be assessed jointly. The article evaluates the diachronic backdrop and parameters appropriate for classificatory categories. Special attention is paid to the criteria applied by aspectologists to determine aspect pairs and to aspect triplets. The assessment ends up with a paradox resulting from Maslov's criteria of 'trivial pairednessʼ, which require not only identical lexical meaning, but an ontology for which telic events are the sole basis in the derivation of aspect pairs.